EMPRETEC women in business award 2012 (UN New York)
Presents the awardees for the Empreten women in business awards which are presented biannually to women trained by Empretec, who have excelled in developing innovative business ideas, providing jobs and increasing income in their communities.
Keywords: ENTREPRENEURSHIP